Ultrasonic Studies of Molecular Interactions in Aqueous Electrolytic Solutions at Different Temperatures - Shinde, B. R.; Jadhav, K. M. (New Approaches in Engineering Research Vol. 11, 2021)
A number of researchers have studied acoustical properties of solutions containing transition metal ions. In this chapter, Acoustical parameters such as adiabatic compressibility’s, specific acoustic impedances, intermolecular free lengths and solvation numbers have been calculatedusing standard relations from measured values of Ultrasonic velocities, densities and viscosities in wide range of concentrations at 303.15, 308.15, 313.15 and 318.15K temperatures for ZnSO4 + water system to study the ion-solvent interactions. With increasing temperature and Zn++ ion concentration in water, ion-solvent interactions are shown to increase. Ion-solvent interactions are weak in very dilute solutions, but U increases steadily at moderate concentrations, indicating that ion-solvent interactions increase with concentrations, implying that ion-solvent interactions increases with concentrations suggesting structure promoting nature of Zn++ ions in cluster of water molecules.